Evaluación de la vulnerabilidad estructural ante sismos en el edificio de la Facultad de Ciencias de la Educación, Sociales, Filosóficas y Humanísticas de la Universidad Estatal de Bolívar (UEB), en el periodo septiembre-diciembre 2024 - Reinoso Torres, Edwin Elian (2025)
The present research seeks to determine the structural vulnerability to earthquakes in the building system of the Faculty of Education Sciences of the State University of Bolivar, built in 1995, with standards of that time, for the first part of this research project vulnerability was evaluated, using the FEMA-154 form, by visual inspection, according to the safety index is of low vulnerability when the final score is SL1>Smin, so the result obtained is 1. 3, justifying the level of structural vulnerability, this does not mean that the building is 100% free of suffering structural failures, being necessary to perform concrete resistance tests with the use of the sclerometer, this will help to have an idea and average of the value of the concrete, to proceed to use the CYPECAD software, which will help to justify the idea to defend, in which it mentions that the use of nonlinear dynamic analysis, allows to have an accurate idea of the behavior of the building in an earthquake, this is given because the software models the structure from the foundation, beams, slabs, columns, loads, etc.